Draft Annual Plan 1983-84 Volume II (Statements) Uttar Pradesh - Planning Commission (Planning Commission, 1983)
Name of Projects with brief description, location and districts benefited. In case of multi-purpose and inter State projects, details of sharing of cost and benefits among various purposes and States may be indicated.
Government of Uttar Pradesh, Planning Department